2008
DOI: 10.1152/jn.01112.2006
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Grip: Anticipatory and Reactive EEG Responses to Load Perturbations

Abstract: Previous behavioral work has shown the existence of both anticipatory and reactive grip force responses to predictable load perturbations, but how the brain implements anticipatory control remains unclear. Here we recorded electroencephalographs while participants were subjected to predictable and unpredictable external load perturbations. Participants used precision grip to maintain the position of an object perturbed by load force pulses. The load perturbations were either distributed randomly over an interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The observed changes in the electrical activity of muscles suggest that the CNS assesses the effect of involvement of the APAs and generates or scales down CPAs accordingly. Such assessment and utilization of anticipatory activity resulting in reduced compensatory corrections following a perturbation have also been reported in tasks involving precision grip maintenance in sitting (Kourtis et al, 2008). Thus, it can be suggested that while dealing with perturbations, the general rule applied by the CNS is to optimally use anticipatory corrections if and when possible, resulting in appropriate scaling down of compensatory activity.…”
Section: Discussionmentioning
confidence: 79%
“…The observed changes in the electrical activity of muscles suggest that the CNS assesses the effect of involvement of the APAs and generates or scales down CPAs accordingly. Such assessment and utilization of anticipatory activity resulting in reduced compensatory corrections following a perturbation have also been reported in tasks involving precision grip maintenance in sitting (Kourtis et al, 2008). Thus, it can be suggested that while dealing with perturbations, the general rule applied by the CNS is to optimally use anticipatory corrections if and when possible, resulting in appropriate scaling down of compensatory activity.…”
Section: Discussionmentioning
confidence: 79%
“…Cortical integrative mechanisms were also shown to be involved in the modulation of the cutaneous long-latency reflex amplitude by Kourtis et al (2008). In this study, subjects had to maintain a grip despite load force perturbations, and the authors investigated the effect of the perturbation predictability on the cutaneous long-latency reflex.…”
Section: Discussionmentioning
confidence: 99%
“…However, they reported that the ERP amplitude increased with the LLSR amplitude, contrasting with the present results. This could be due to the fact that, in the experiment by Kourtis et al (2008), subjects were required to maintain the motor output, whereas here, subjects had to change their reaction to the perturbation. As pointed out by other studies (Abbruzzese et al, 1985;Shemmell et al, 2009), stretch reflex modulations induced by changes in mechanical environment and by verbal instruction seem to be mediated by different neural pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed our results, in agreement with the study of Earles et al (2001), suggest that elderly adults rely more on the central command than on peripheral mechanisms to regulate motor output. By integrating the response to the somatosensory input at a cortical level, a transcortical reflex pathway may provide an input onto the motor neurone pool more adapted to the specificities of the task than a purely segmental pathway (Chan 1983;Kourtis et al 2008;Zuur et al 2009). However, further studies are required to determine the precise neural mechanisms explaining the greater age-related area of the supraspinal reflexes.…”
Section: Age-related Changes In the Area Of The Stretch Reflex Componmentioning
confidence: 99%